On the natural attenuation of leaching hexavalent chromium by ambient-soil and associated health-risks: characterization and adsorption studies - Shreya Ganguly; Sayantan Ganguly (Results in Engineering, 2025)
Hexavalent chromium [Cr(VI)] contamination in the subsurface presents a significant challenge to environmental sustainability and public health. Its mobility and dispersion are highly dependent on soil properties, which can either promote natural attenuation through adsorption by the soil particles, or create pathways that facilitate its transport, increasing the risk of groundwater pollution. This study evaluates the natural ambient soil’s potential to adsorb Cr(VI) and identifies key influencing factors such as dose, pH, contact time, and initial Cr(VI) concentration to optimize adsorption efficiency. To obtain deeper insights, Electrical Resistivity Tomography (ERT) is utilized to evaluate the lithological features of the study area, complemented by advanced characterization techniques to analyse the soil’s microstructural characteristics and chemical constituents. Adsorption isotherm and kinetic studies were conducted to elucidate the adsorption mechanism and identify the rate-limiting steps, respectively. Furthermore, the study quantifies potential risks to human health, including carcinogenic and non–carcinogenic effects associated with residual Cr(VI) concentrations in contaminated water, underscoring the critical need for effective remediation strategies and the restoration of public health safety. The study findings revealed a residual Cr(VI) concentration of 0.583 mg/L–significantly exceeding the World Health Organization’s (WHO’s) permissible limit of 0.05 mg/L. This alarming level underscores the critical need for health–risk assessments, which indicated a “very high” total cancer risk and “very high” non–cancer risks for both the male and female populations.